Consistent provisions mitigate exposure to sexual risk and HIV among young adolescents in South Africa - Toska, E; Campeau, L; Cluver, L; Orkin, F; Berezin, M; Sherr, L; Laurenzi, C; Bachman, G (Springer, 2019)
Exposure to sexual risk in early adolescence strongly predicts HIV infection, yet evidence for prevention in young adolescents is limited. We pooled data from two longitudinal South African surveys, with adolescents unexposed to sexual risk at baseline (n = 3662). Multivariable logistic regression tested associations between intermittent/consistent access to eight provisions and reduced sexual risk exposure. Participants were on average 12.8 years, 56% female at baseline. Between baseline and follow-up, 8.6% reported sexual risk exposure. Consistent access to caregiver supervision (OR 0.53 95%CI 0.35–0.80 p = 0.002), abuse-free homes (OR 0.55 95%CI 0.37–0.81 p = 0.002), school feeding (OR 0.55 95%CI 0.35–0.88 p = 0.012), and HIV prevention knowledge (OR 0.43, 95%CI 0.21–0.88 p = 0.021) was strongly associated with preventing early sexual risk exposure. While individual factors reduced the odds of sexual risk exposure, a combination of all four resulted in a greater reduction, from 12.9% (95%CI 7.2–18.7) to 1.0% (95%CI 0.2–1.8). Consistent access to provisions in early adolescence may prevent sexual risk exposure among younger adolescents.